Dysphemism Manifestation: Disassembly Ganyang Malaysia in Indonesian Football News Headlines - NFN Aswan; Anang Santoso; Moch. Syahri (SUAR BETANG, 2023)
In recent decades (1959-2023), the phrase ganyang Malaysia has been widely used by the media to frame the confrontation of Indonesia and Malaysia. Over time, the media has employed this phrase in various contexts, including Indonesian football headlines. So far, research related to the phrase ganyang Malaysia in the context of semantic studies has not shown significant results, warranting further investigation. Focus of this research is to examine the use of the phrase ganyang Malaysia in Indonesian football news headlines, based on its usage in media, meanings, and history. The method employed in this study was qualitative and utilized a semantic study approach. The research data consisted of 40 Indonesian football news headlines obtained from 10 online media. Indonesian media uses the phrase ganyang Malaysia to convey a sense of superiority and the euphoria. In terms of its meaning and history, phrase ganyang Malaysia manifests as a form of jargon disfeminism with the purpose of characterizing, emphasizing, and representing unfavorable situations. The manifestation of disfemism in the phrase ganyang Malaysia serves as empirical evidence that sports can be a means of expressing emotions, national identity, and collective sentiments within society. AbstrakFrasa ganyang Malaysia dalam beberapa dekade ini (1959-2023) banyak digunakan media massa dalam membingkai konfrontasi Indonesia dengan Malaysia. Dalam perkembangannya, media massa menggunakan frasa tersebut dalam berbagai konteks, salah satunya tampak pada judul berita sepak bola Indonesia. Sejauh yang ditelusuri, belum ada penelitian secara spesifik mengungkapkan bagaimana frasa ganyang Malaysia pada judul berita. Dengan demikian, penelitian ini bertujuan untuk meneliti frasa ganyang Malaysia dalam judul berita sepak bola berbasis berdasarkan perspektif penggunaannya di media massa, makna, dan sejarah. Jenis metode penelitian yang diterapkan adalah kualitatif dengan pendekatan kajian semantik. Data penelitian adalah 40 judul berita sepak bola Indonesia yang didapatkan dari 10 media massa daring (media mainstream). Ditemukan bahwa frasa ganyang Malaysia digunakan media massa Indonesia untuk menampilkan superior dan euforia kemenangan Indonesia atas Malaysia atau kekalahan Malaysia dari Indonesia dan negara lain. Ditinjau dari makna dan sejarahnya, frasa ganyang Malaysia memanifestasikan disfemisme berbentuk jargon dengan tujuan untuk karakterisasi, penekanan, dan representasi situasi buruk. Manifestasi disfemisme dalam frasa ganyang Malaysia menjadi bukti impiris bahwa olahraga dapat menjadi sarana untuk mengekspresikan emosi, identitas nasional, dan sentimen kolektif dalam masyarakat.